AN IMPROVED CYBER SECURITY FRAMEWORK FOR EDUCATION INSTITUTIONS IN INDONESIA - Hidayatulloh, Syarif; Abd Rahman, Aedah (Universitas Efarina, 2019)
One of the trends in the world of Education is Education technology. The COVID-19 pandemic forces us to accelerate using educational technology to keep the learning process in educational institutions around the world running. However, in adapting and using educational technology, it turns out that there is a factor of concern, namely cyber security. Because almost all educational technology platforms use the internet, cyber security is something that we inevitably have to deal with. Moreover, it turns out that during this covid19 pandemic, cybersecurity attacks have also increased along with the increase in the use of educational technology. Due to the high number of attacks and a large number of security holes in the Education technology platform adopted by educational institutions, So in this study, the authors will evaluate existing standards, models, and frameworks, identify fundamental and critical cybersecurity problems in several educational institutions in Indonesia, and propose a better security framework to address cybersecurity problems in educational technology in institutions.